UNESCO’s Atlas on Endangered Languages and the Local Context - Poshka Agim (SEEU Review, 2021)
This article analyses the overall development of the endangered language around the world in reference to UNESCO’s Atlas of World Endangered Languages and reflects on the local context. The focus to local context refers to the current territory of North Macedonia in which it is believed there are 7 endangered languages such as: Adyge, Aromanian, Gagauz (South Balkans), Megleno-Romanian, Judezmo, Romani and Torlak. These languages are classified as endangered but are still spoken in the country. The article also reflects on the status of the Albanian language in North Macedonia by drawing comparisons with two other language varieties such as Arberesh which spoken in Southern Italy and Arvanitika spoken in Greece. The challenges that these minority languages have faced in particular countries should serve as a guide in designing effective language policies in North Macedonia in order for the language not be endangered. In the last section the article report on the phenomena of Globalization in which English has become the global language and at the same time has accelerated the loss of many native languages around the globe.